Dissolved and particulate trace metal micronutrients under the McMurdo Sound seasonal sea ice: basal sea ice communities as a capacitor for iron - Noble, Abigail E.; Saito, Mak A.; Moran, Dawn M.; Allen, Andrew (Frontiers in Chemistry, 2013)
Dissolved and particulate metal concentrations are reported from three sites beneath and at the base of the McMurdo Sound seasonal sea ice in the Ross Sea of Antarctica. This dataset provided insight into Co and Mn biogeochemistry, supporting a previous hypothesis for water column mixing occurring faster than scavenging. Three observations support this: first, Mn-containing particles with Mn/Al ratios in excess of the sediment were present in the water column, implying the presence of bacterial Mn-oxidation processes. Second, dissolved and labile Co were uniform with depth beneath the sea ice after the winter season. Third, dissolved Co:PO43- ratios were consistent with previously observed Ross Sea stoichiometry, implying that over-winter scavenging was slow relative to mixing. Abundant dissolved Fe and Mn were consistent with a winter reserve concept, and particulate Al, Fe, Mn, and Co covaried, implying that these metals behaved similarly. Elevated particulate metals were observed in proximity to the nearby Islands, with particulate Fe/Al ratios similar to that of nearby sediment, consistent with a sediment resuspension source. Dissolved and particulate metals were elevated at the shallowest depths (particularly Fe) with elevated particulate P/Al and Fe/Al ratios in excess of sediments, demonstrating a sea ice biomass source. The sea ice biomass was extremely dense (chl a >9500 μg/L) and contained high abundances of particulate metals with elevated metal/Al ratios. A hypothesis for seasonal accumulation of bioactive metals at the base of the McMurdo Sound sea ice by the basal algal community is presented, analogous to a capacitor that accumulates iron during the spring and early summer. The release and transport of particulate metals accumulated at the base of the sea ice by sloughing is discussed as a potentially important mechanism in providing iron nutrition during polynya phytoplankton bloom formation and could be examined in future oceanographic expeditions.